Gall-inducing insects of an Araucaria Forest in southern Brazil - Tiago Shizen Pacheco Toma; Milton de Souza Mendonça Júnior (Revista Brasileira de Entomologia, 2013)
Gall-inducing insects of an Araucaria Forest in southern Brazil. Diversity of galling insects is reported for the first time in an Araucaria Forest site. We address gall characteristics, host plant identification and the inducer identification and provide additional information about sites of gall occurrence in a mosaic of continuous forest and natural forest patches. After 40h of sampling we found 57 species of five insect orders, the majority of them Diptera (Cecidomyiidae), galling 43 host plant species, which in turn belonged to 18 host plant families. Stem and buds together, compared to leaves, harbored more galls, which were mostly glabrous, isolated, fusiform and green. Myrtaceae, Asteraceae and Melastomataceae were the most representative host families. Similarities in gall characteristics to what has been reported in the literature probably result from spatial correlation in a larger scale driven by ecological and evolutionary processes.